2011
DOI: 10.4012/dmj.2010-095
|View full text |Cite
|
Sign up to set email alerts
|

A biocompatible model for evaluation of the responses of rat periapical tissue to a new zinc oxide-eugenol sealer

Abstract: We aimed to establish an experimental animal model to evaluate materials for endodontic therapy. We focused on the biocompatibility of new paste-type zinc oxide-eugenol (ZOE) sealer. The results of this sealer were compared with those of conventional powder/liquid ZOE and eugenol-free sealers. The molars of Wistar rats were extracted and repositioned in the original socket after application of the sealers on the root apices. Mild inflammation occurred in the periapical tissue of the replanted teeth with both Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Regarding the morphological changes of fibroblasts in the present study, the Endofill showed round-shaped fibroblasts with few processes and large acellular areas. Previous studies attributed the toxicity of ZOE-based cements to the eugenol and zinc ions released by the material in a wet environment (9,25). Therefore, one may suggest that the zinc and eugenol components released in the culture medium from the highly soluble cement Endofill may be responsible for higher cytotoxicity caused by this sealer to the cultured cells when compared to the other cements tested in the present investigation.…”
Section: Discussionmentioning
confidence: 44%
“…Regarding the morphological changes of fibroblasts in the present study, the Endofill showed round-shaped fibroblasts with few processes and large acellular areas. Previous studies attributed the toxicity of ZOE-based cements to the eugenol and zinc ions released by the material in a wet environment (9,25). Therefore, one may suggest that the zinc and eugenol components released in the culture medium from the highly soluble cement Endofill may be responsible for higher cytotoxicity caused by this sealer to the cultured cells when compared to the other cements tested in the present investigation.…”
Section: Discussionmentioning
confidence: 44%
“…[2122] Rat subcutaneous implantation studies are acceptable experimental models for this assessment[23] and the inert nature of polyethylene tubes makes them suitable for implantation studies, so implantation of polyethylene or silicon tubes filled with endodontic materials into subcutaneous connective tissue of rats simulates in situ conditions of the materials. [24]…”
Section: Discussionmentioning
confidence: 99%
“…Ten microliters of these mixed materials were applied to each of the five root apices of M1 ( Fig. 1) using a 27-G needle (Terumo Company Limited, Tokyo, Japan) attached to a 1-mL plastic syringe 23) . The extracted tooth with materials was immediately repositioned in the original socket after the confirmation of hemostasis; these were classified as the "experimental groups".…”
Section: Animal Experimentsmentioning
confidence: 99%
“…The histomorphological parameters used in this study were based upon previously described criteria 23,25,26) . For the determination of scores, sections were evaluated according to four parameters.…”
Section: Histomorphological Parametersmentioning
confidence: 99%
See 1 more Smart Citation